PERENCANAAN KOMUNIKASI BADAN PUSAT STATISTIK KOTA PEKANBARU DALAM MENSOSIALISASIKAN TENTANG PROGRAM SENSUS EKONOMI 2016 - Yoppi Kristianto; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Economic census is collecting data for all business units / companies completelywithin regional of a country. All of the collected information are useful to analyze theperforma and economic structure of a country. Statistic Center Institution (BPS) Pekanbarucity are the one who communicate about this to the civil. Communication plan which beendone by BPS are by socialized economic census 2016 and then menentukan which public,create the message, and choosing media partner on socialized economic census 2016 activity.This study aims to analyzed how the communication plan of statistic center institutionPekanbaru city on socializing economic census 2016 program.This study used qualitative methods with description approach. The research wasdone in BPS Pekanbaru city office at Rawa Indah street. The informants in this study wascollected by using purposive sampling technique. The data collected are primary data alsosecondary data. The data collected by doing observation, interviewed, and documentation.This research was analyzed with Miles and Huberman data analyzes also confirmed by doingperpanjangan keikutsertaan dan triangulasi.The results of this study indicate that the planning of communication used by BPSPekanbaru in socializing the 2016 economic census programs is using communicationplanning model groove mark ? in determining the terms of audience, BPS Pekanbarusocialize economic census in 2016 to categorize all society who have the characteristics ofsmall businesses and large businesses, in terms of the draft message BPS Pekanbaru extendan invitation to participate in the implementation of the economic census in 2016, then interms of media selection BPS Pekanbaru select group communication and mediatedcommunication, printed and mass media, and in terms of the evaluation of the economiccensus program 2016, BPS Pekanbaru evaluate the programs in order to determine thesuccess of the 2016 economic census programs which been implemented for the fourth time.The purpose of the communication planning is to formulate measures to realize the objectivesof the economic census program in 2016.Keyword: communication planning, economic sensus 2016, BPS Kota Pekanbaru